SHORT COMMUNICATION: DAMAGE TO THE HISTOLOGICAL STRUCTURE OF MICE LIVER (Mus musculus) DUE TO EXCESSIVE CONSUMPTION OF SODIUM CHLORIDE - Rizqi Nur Ardiansyah; Arum Setiawan; Yuanita Windusari (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Salt or sodium chloride (NaCl) is used in everyday life mainly to give food taste. Salt is hepatotoxic, so excessive use of salt has an impact on the liver. The liver is one part of the organ that has an important role in the body's metabolism, especially in neutralizing toxins. The liver is composed of hepatocytes. There are 60% hepatocytes of the total cells in the liver. Hepatocytes are the main cells responsible for the central role of the liver in metabolism. Liver function becomes very vulnerable to damage because it continuously neutralizes toxins. Such damage can occur and affect the structure and function of the liver. This study was conducted to determine the structural abnormalities of hepatocytes that occur in the liver of mice (Mus musculus) due to excessive salt consumption. The method used in this study was a CRD (completely randomized design) method consisting of 1 control group and 3 treatment groups by sodium chloride (NaCl) with 6 replications. The parameter in this study was the level of hepatocyte damage in the liver of mice (Mus musculus). Hepatocyte damage that occurred was observed through histological preparations with Hematoxylin Eosin (HE) staining. The results of this study indicate that hepatocyte cell damage in the liver of mice (Mus musculus) increases due to continuous administration of excess sodium chloride (NaCl).